2021
DOI: 10.1111/jjns.12415
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in patients with nonalcoholic fatty liver disease: Structure and related factors focusing on illness uncertainty

Abstract: AimPatients with nonalcoholic fatty liver disease (NAFLD) have a low quality of life (QOL) and illness uncertainty. This study examined the structure of QOL and associated factors, including illness uncertainty, among individuals with NAFLD.MethodsA cross‐sectional survey was conducted using a self‐administered questionnaire for outpatients with NAFLD. QOL was measured using the Short Form‐8. Dietary habits, physical activity level, illness uncertainty, health locus of control, and knowledge of NAFLD were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…In this study, patients’ anxiety, depression and impaired QoL were correlated with uncertainty in illness, as is exhibited in studies related to other diseases (Chen et al., 2018 ; Ozawa et al., 2021 ; Pahlevan Sharif, 2017 ; Parker et al., 2016 ). Patients receiving MHD tended to appraise uncertainty in illness as a threat giving rise to psychological stress rather than an opportunity (Ahn et al., 2017 ; Chen et al., 2018 ; Parker et al., 2016 ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, patients’ anxiety, depression and impaired QoL were correlated with uncertainty in illness, as is exhibited in studies related to other diseases (Chen et al., 2018 ; Ozawa et al., 2021 ; Pahlevan Sharif, 2017 ; Parker et al., 2016 ). Patients receiving MHD tended to appraise uncertainty in illness as a threat giving rise to psychological stress rather than an opportunity (Ahn et al., 2017 ; Chen et al., 2018 ; Parker et al., 2016 ).…”
Section: Discussionsupporting
confidence: 67%
“…Though many studies concerning patients with cancer, heart disease and other chronic diseases widely reported the association between uncertainty in illness and anxiety, depression and QoL, there were limited studies specific to MHD confirm this relationship in China (Chen et al., 2018 ; Ozawa et al., 2021 ; Pahlevan Sharif, 2017 ). Thus, we hypothesize that patients receiving MHD suffered uncertainty in illness was related to anxiety, depression and QoL positively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the risk of progression to end-stage liver disease, NAFLD can also impact life quality in many ways in the early stage. It has been reported that demographics, clinical parameters and severity of disease were all related to QoL [ 8 ]. Few studies have explored the influence of health-related fitness on QoL of NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the accumulating evidence, NAFLD patients experience an impaired QoL, which is significantly lower than the general population [ 40 ] and hepatitis C patients [ 41 ]. Lower QoL of NAFLD has been verified to be related with elder age, female, low income and educational level, obesity, T2DM, fibrosis and cirrhosis, but not affected by liver enzymes or serum albumin [ 8 ]. In our population, the dimensions were also not affected by steatosis severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation